If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 7) + -6x = 3x + 23 Reorder the terms: 5(7 + 3x) + -6x = 3x + 23 (7 * 5 + 3x * 5) + -6x = 3x + 23 (35 + 15x) + -6x = 3x + 23 Combine like terms: 15x + -6x = 9x 35 + 9x = 3x + 23 Reorder the terms: 35 + 9x = 23 + 3x Solving 35 + 9x = 23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 35 + 9x + -3x = 23 + 3x + -3x Combine like terms: 9x + -3x = 6x 35 + 6x = 23 + 3x + -3x Combine like terms: 3x + -3x = 0 35 + 6x = 23 + 0 35 + 6x = 23 Add '-35' to each side of the equation. 35 + -35 + 6x = 23 + -35 Combine like terms: 35 + -35 = 0 0 + 6x = 23 + -35 6x = 23 + -35 Combine like terms: 23 + -35 = -12 6x = -12 Divide each side by '6'. x = -2 Simplifying x = -2
| 141=0+3.3t | | 8(x+3)=8(x+13) | | ln(x)-ln(x-7)=ln(7) | | -9z-8=-z+6-z | | 3x-3=5x+13 | | (-2c-5)-(6c+20)= | | 8/9x-5=27 | | 9+4m=10+5m | | 141=o+3.3t | | (x+10)+2x+x=3000 | | 7x+14=-4x-18 | | 5x+10=-8x-20 | | 28.25=8+1.75x+8.00 | | -9-10j=9-8j | | -4+5s+3=7s-9 | | 4x^2y+28xy-8y=0 | | 2-10y=9-3y | | -3u+1=10-2u | | 7(10x+1)=70x-9 | | 27=3-2x | | 4(x+2)=4(x+10) | | 5-5-7k=-10k-10 | | 9.5+2x=32.7 | | x+2/2=8 | | 45+24x+3x^2=0 | | 8x-32-5x=37 | | 180=2x(3x+20) | | 14x+7y+21=0 | | -83+9x=25 | | 3(7x-4)= | | 7x+12=-5x-16 | | 8*2-5*3(-21)= |